2021
DOI: 10.3390/ijms222312860
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery Caused by Human Adipose Tissue Mesenchymal Stem Cell-Derived Extracellular Vesicles Administered 24 h after Stroke in Rats

Abstract: Ischemic stroke is a major cause of death and disability, intensely demanding innovative and accessible therapeutic strategies. Approaches presenting a prolonged period for therapeutic intervention and new treatment administration routes are promising tools for stroke treatment. Here, we evaluated the potential neuroprotective properties of nasally administered human adipose tissue mesenchymal stem cell (hAT-MSC)-derived extracellular vesicles (EVs) obtained from healthy individuals who underwent liposuction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 78 publications
(126 reference statements)
1
14
0
Order By: Relevance
“…35 In addition to bone marrow-derived MSCs, EVs from adipose-derived MSCs also exert positive effects on the reconstruction of blood vessels and functional recovery in the adult brain. 36 Wide availability of MSC-EVs from different tissues provides additional options for MSC-EV administration in humans. Compared with intravenous infusions of hMSCs, intranasal administration of EVs is less invasive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In addition to bone marrow-derived MSCs, EVs from adipose-derived MSCs also exert positive effects on the reconstruction of blood vessels and functional recovery in the adult brain. 36 Wide availability of MSC-EVs from different tissues provides additional options for MSC-EV administration in humans. Compared with intravenous infusions of hMSCs, intranasal administration of EVs is less invasive.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with intravenous infusions of hMSCs, intranasal administration of EVs is less invasive. 36 Thus, we think MSCs-EVs could be a promising therapeutic strategy that mimics the effect of MSCs transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…MSC-derived products have already been tested in stroke models. Intranasal injection of human AT-MSC-derived Evs 24 h after a thermocoagulation ischemic lesion-induced a reduction in infarct volume and re-stabilization of vascularization in the peri-infarct area, culminating in behavioral improvement (Rohden et al, 2021 ). Recently, Zhao et al ( 2020 ) showed that exosomes isolated from rat BM-MSCs overexpressing microRNA-223-3p injected into the tail vein 24 h and 14 days after MCAO induced an improvement in NSS, in relation to naïve-BM-MSC exosomes, but both groups were significantly different from the vehicle.…”
Section: Msc Therapy In Neurological Diseasesmentioning
confidence: 99%
“…This has included studies in ischemic and hemorrhagic strokes (Xin et al, 2013a;Xin et al, 2013b;Doeppner et al, 2015a;Chen et al, 2016;Otero-Ortega et al, 2017;Venkat et al, 2019;Mahdavipour et al, 2020;Rohden et al, 2021) and perinatal brain injury (Drommelschmidt et al, 2017;Sisa et al, 2019;Kaminski et al, 2020), some treated with intranasal MSC-EVs (Thomi et al, 2019a;Thomi et al, 2019b). Importantly, for this discussion regarding nasal sEV therapy of the neuro-psychiatric aspects of LCS, this includes the treatment of various neurodegenerative diseases with nasal sEVs, that has succeeded in diminishing pathologies in animal models of Parkinson's disease (Laso-Garcia et al, 2018;Clark et al, 2019;Narbute et al, 2019;Chen et al, 2020;Jafarinia et al, 2020;Zhu et al, 2021), amyotrophic lateral sclerosis (ALS) (Bonafede et al, 2016;Gugliandolo et al, 2019), and Alzheimer's disease (Alvarez-Erviti et al, 2011;Ding et al, 2018a;Elia et al, 2019;Reza-Zaldivar et al, 2019;Losurdo et al, 2020a;Ma et al, 2020a;Cone et al, 2021a); as well as psychiatric disorders such as autism (Perets et al, 2018;Alessio et al, 2020) and schizophrenia (Tsivion-Visbord et al, 2020), and further in neurotraumas such as traumatic brain injury (Patel et al, 2018;Ni et al, 2019;Williams et al, 2019;Sun et al, 2020;Williams et al, 2020), spinal cord injury …”
Section: Productive Nasal Therapy Employing Mesenchymal Stromal Cell-...mentioning
confidence: 99%